PERSEPSI PENGGUNA LAPORAN KEUANGAN ATAS FAKTORâFAKTOR YANG MEMPENGARUHI INDEPENDENSI PENAMPILAN AUDITOR BPK - , Geger Adelia; , Prof. Dr. Abdul Halim, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to examine the influence of personal relationships, frequency of audits, auditor income and facilities provided by auditee on independence in appearance of the Supreme Audit Institution (BPK) Auditors in terms of user of local government financial statements perception and the differences of perception between users of local government financial statements in Semarang. The method used was a survey with a questionnaire as a data collection tool. The population used is users of the local governmentâs financial statements and the selected sample consisted of three groups, namely academics, BPKP auditors representing financial supervision agencies and the public (NGO activists, practitioners and community leaders) totaling 90 samples. Analysis using descriptive statistics and multiple regression, and hypothesis testing include simultaneous test (test statistic F) and partial test (test statistic t). The research concludes that only the personal relationships that affect the auditors independence in appearance significantly, while the other three variables had no significant effect. In addition there is a difference in perception between academics with regulatory agencies and the general public.